Colombia: a country where people die in vain? an anthropological interpretation of the life and works of the comedian jaime garzón (1960-1999) (2011)
Under the light of the mimetic theory of René Girard, the life and works of the comedian Jaime Garzón is shown as a prophetic motion revealing the causes of violence in Colombia. Celebrating this artist.s memory stands a civic duty: an instrument that contributes to building an educated public opinion and a thought for peace, rooted in the country.s culture. This article is a contribution on religion in anthropological terms and opens new perspectives to regard the Christian faith as a transcendent dimension that manifests itself on the pathway to social justice.